The Tick Microbiota Dysbiosis Promote Tick-Borne Pathogen Transstadial Transmission in a Babesia microti–Infected Mouse Model - Wei, Nana; Cao, Jie; Zhang, Houshuang; Zhou, Yongzhi; Zhou, Jinlin (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Ticks are obligate hematophagous ectoparasites. They are important vectors for many pathogens, of both medical and veterinary importance. Antibiotic residues in animal food are known, but very little is known about the effects of antibiotic residues in animals on the microbiome diversity of ticks and tick-borne pathogen transmission. We used a Haemaphysalis longicornis infested mouse model to evaluate the effect of antibiotic usage on tick microbiome. Nymphal ticks were fed on an antibiotic cocktail-treated or water control mice. Adult ticks molted from nymphs fed on the antibiotic cocktail-treated mouse had a dysbiosed microbiota. Nymphal ticks were also fed on a B. microti-infected mice that had been treated with antibiotic cocktail or water. We found that the B. microti infection in adult ticks with a dysbiosed microbiota (44.7%) was increased compared to the control adult ticks (24.2%) by using qRT-PCR targeting 18S rRNA gene. This may increase the risk of tick-borne pathogens (TBPs) transmission from adult ticks to a vertebrate host. These results show that an antibiotic-treated mouse can induce tick microbiota dysbiosis. Antibiotic treatment of B. microti-infected mouse poses the possibility of increasing transstadial transmission of B.microti from the nymph to the adult H. longicornis. These findings suggest that B. microti transmission may be exacerbated in high antibiotic usage areas.